Implementación de un biodigestor piloto unifamiliar para la obtención y caracterización de biogás de uso calorífico a base de estiércol vacuno - Chacha Pumasunta, Jesús Manuel (2017)
The manure generated by the cattle in the rural area is not used in the best way, the farmers use it as fertilizer for the sowing, they do not know its negative effects on the environment, besides the inconvenience they have to transport a thermal energy source that is used for domestic, with these elements analyzed appear the initiative to implement a polyethylene biodigestor based on bovine manure for the biogas generation in Hacienda Terán located in La Dolorosa, Belisario Quevedo Parish, which it is based in the process of anaerobic digestion, in addition to the research was reinforced knowledge about renewable energy in rural areas and a great impact and progress in the change of matrix energy, as a starting point was analyzed fresh manure, obtaining 13.7% of total solids, 25: 1 in relation to C: N necessary for sizing calculations and other elements used in the characterization, in addition it established 100 kg of mixture with the quantification of the manure in a period of 10 days, in order to elevate the low temperatures of the region, it built a greenhouse for obtaining an average of 25.38 ° C….